An analysis of flanders interaction categories in english teaching learning class in grade five of SDN Keputran V Yogyakarta in the academic year 2006/2007 / Siti Mufrihah Hayati - SITI Mufrihah Hayati (Universitas Ahmad Dahlan, 2007)
x, 61 lembar ; 29,5 cm.